Detrital zircon U–Pb ages of Tertiary sequences (Palaeocene‐Miocene): Inner Fold Belt and Belt of Schuppen, Indo‐Myanmar Ranges, India. Issue 12 (12th April 2022) - Ding, Lin; Goswami, Tapos K.; Cai, Fu Long; Baral, Upendra; Sarmah, Ranjan K.; Bezbaruah, Devojit
Abstract : The along‐strike heterogeneity in the tectonics of Himalaya is well recognized; however, the eastern segment of Himalaya is less studied compared to the other segments. This study combines the comprehensive field data, as well as the U–Pb geochronology of sandstone samples from the Indo‐Burma Range (east India). The study shows that the Lower Disang Formation was deposited in an open marine environment with a steep gradient during the Late Cretaceous to Mid‐Eocene, accommodating the detritus solely from an Indian source. Furthermore, during the Early to Late Eocene interval, the sedimentary basin changed to a shallow marine shelf when the sediments from Himalayan as well as trans‐Himalaya were deposited. The Upper Disang Formation must have been deposited just before or during the collision process between the Indian and Asian plates. After the India‐Asian collision, there was a remnant ocean, in which the sediments of the Barail and Surma groups were deposited in the shallow marine to deltaic environments. The Tethys Ocean completely dried out in the Late Miocene resulting in a change from marine to fluvial environments, which facilitated the deposition of the sandstones of the Tipam Formation. Based on the U–Pb ages, the Palaeogene basin history in the Indo‐Burma Range was unlike the central Himalaya, that is, the detritus were mainly sourced from the Burmese Plate and adjoining magmatic rocks. Abstract : During Late Cretaceous to Mid‐Eocene the sedimentary environment was open marine with a steep gradient. While in the Early to Late Eocene it changed to a shallow marine shelf and onset of the India‐Asian collision, which finally ended by the deltaic environment which if followed by shallow marine. The Paleogene basin history in the Indo‐Burma Range was unlike the central Himalaya, i.e. the detritus were mainly sourced from the Burmese Plate and adjoining magmatic rocks. Eastern Himalayan foreland basin tectonics